2021
DOI: 10.1186/s40659-021-00332-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MALAT1 regulates cell proliferation and apoptosis via miR-135b-5p/GPNMB axis in Parkinson’s disease cell model

Abstract: Backgrounds Parkinson’s disease (PD) is a common age-related neurodegenerative disorder worldwide. This research aimed to investigate the effects and mechanism underlying long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in PD. Methods SK-N-SH and SK-N-BE cells were treated with MPP+ to establish the MPP+-stimulated cell model of PD, and MALAT1 expression was determined. Then, the effects of MALAT1 depletion on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…LncRNAs can directly interact with miRNAs as competitive endogenous RNAs, thereby regulating their expression levels and activities [ 44 ]. Lv et al revealed that miR-135b-5p is a target of MALAT1, and MALAT1 regulates the cell viability by regulating miR-135b-5p expression in Parkinson’s disease [ 45 ]. Jia et al showed that MALAT1 is involved in ischemia-reperfusion injury via miR-195a-5p [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs can directly interact with miRNAs as competitive endogenous RNAs, thereby regulating their expression levels and activities [ 44 ]. Lv et al revealed that miR-135b-5p is a target of MALAT1, and MALAT1 regulates the cell viability by regulating miR-135b-5p expression in Parkinson’s disease [ 45 ]. Jia et al showed that MALAT1 is involved in ischemia-reperfusion injury via miR-195a-5p [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR may also promote apoptosis of neuronal cells through microRNA-126-5p (miR-126-5p)/RAB3A-interacting protein (RAB3IP) axis (Lin et al, 2019 ). Furthermore, MALAT1 contributed to the apoptosis of DAs by combining with miR-124 and microRNA-135-5p (miR-135-5p; Liu W. et al, 2017 ; Lv et al, 2021 ).…”
Section: How Do the Ncrnas Regulate Parkinson’s Disease?mentioning
confidence: 99%
“…MALAT1 expression is also upregulated in PD brains as well as in mouse and cellular models of PD [75,[130][131][132][133][134] and was suggested to promote neuronal apoptosis by acting as a miR-124 sponge [132]. Many studies have reported significant downregulation of miR-124 in PD models, which prevents it from playing its neuroprotective role against dopaminergic cell death, autophagy dysregulation, neuroinflammation, and oxidative damage (Table S1) [135].…”
Section: Malat1mentioning
confidence: 99%
“…Many studies have reported significant downregulation of miR-124 in PD models, which prevents it from playing its neuroprotective role against dopaminergic cell death, autophagy dysregulation, neuroinflammation, and oxidative damage (Table S1 ) [ 135 ]. Furthermore, MALAT1 can contribute to MPP + -induced apoptosis by regulating the miR-205-5p/LRRK2, miR-135b-5p/GPNMB (glycoprotein nonmetastatic melanoma protein B), and miR‐124‐3p/DAPK1 axes (Table S1 ) [ 130 , 131 , 133 ]. Mutations in the LRRK2 kinase gene, described as a frequent cause of both familial and sporadic PD, result in mitochondrial dysfunction, whereas DAPK1 is involved in dopaminergic neuron degeneration in PD [ 130 , 131 , 133 ].…”
Section: Autoimmune and Neurodegenerative Disorder Pathomechanisms Ca...mentioning
confidence: 99%
See 1 more Smart Citation